PENGARUH KUALITAS LAYANAN, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI AYAM DJOEPREK NGRONGGO KOTA KEDIRI - Muhammad Nugroho Al Nawawi; Indah Yuni Astuti; Ririn Wahyu Arida (Cahaya Ilmu Bangsa, 2025)
This research analyzes the influence of service quality, price and promotion on purchasing decisions at Ayam Djoeprek Ngronggo, Kediri City. Quantitative methods were used with a sample of 91 consumers taken randomly Incidental Sampling. Data was collected through questionnaires and analyzed using validity, reliability, classical assumptions, multiple linear regression, R², t test and f test. The results of this research indicate that service quality partially has a significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Price partially has a significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Promotion partially has a significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Meanwhile, Service Quality, Price and Promotion simultaneously have a significant effect on purchasing decisions with a significance value of 0.000 < 0.05.